Os sentidos da reforma agrária no lulismo - Mello, Marcos Paulo Campos Cavalcanti de (2018)
This work aims to understand the displacements of meaning attributed to agrarian reform in the context of the Lula and Dilma governments and their implications for the social demand for agrarian reform in Brazil, especially that organized by the MST. These two questions insert this research in the field of debates about the character and scope of the changes promoted by the national PT governments in rural and in the Brazilian society as a whole, with particular attention to the impacts of these changes on the social struggle in the countryside. This research turns to the federal executive power, since it is the constitutional responsibility for the execution of the agrarian reform policy and, therefore, it is directed to the social and union movements that demand it. At the same time, it also focuses on the most visible social movement of the land reform national struggle in the last thirty years in the sense of perceiving how the agrarian policy of the PT governments implied changes in the repertoire of action of the MST. Methodologically, this work articulates the readings of specialists, the monitoring of the political conjuncture in newspapers, the collection of statistical data, the ethnographic insertion and the analysis of documents. This eclecticism makes it possible to affirm the residual character of the land reform lulista and the contemporary face of the MST, marked by the rise of settlers in its social base.